(untitled) (Hoboken, N.J., 2006)
Master Traders introduces you to an outstanding group of financial experts—from seasoned hedge fund managers to top technical analysts—who discuss the methods they use to tame today’s highly volatile and unpredictable markets. Composed of chapters contributed by leading financial professionals, Master Traders contains a variety of proven strategies and techniques that will give you an edge in the world of stocks, options, and futures
Keywords: Speculation,Stocks,Investment analysis,Phân tích đầu tư chứng khoán